Application of Curriculum and Management in the Existence of Madrasah Diniah Takmiliyah Awaliyah - Asrin, Ahmad; Nahar, Syamsu; Nurmawati (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study aims to analyze the implementation of the curriculum and management of Madrasah Diniah Takmiliyah Awaliyah (MDTA). This research is literary with a library research approach. Data sources are obtained from written works such as books, articles, etc. Then, the data analysis technique in this research emphasizes the process of comparative inference and analysis of the dynamics of observed phenomena using scientific logic. The research results show that curriculum implementation and management are very important elements for MDTA educational institutions. Researchers agree with several previous research findings, which state that MDTA management includes a curriculum development management process carried out through the stages of planning, organizing, implementing, and evaluating. Furthermore, implementing the curriculum at MDTA is a strategy for achieving the institution's vision, mission, and goals. The curriculum review at MDTA consists of three stages. However, to maintain the existence of MDTA, curriculum uniformity and strengthening aspects of mastering more Islamic sciences are needed. At the same time, more modern MDTA governance or management and complete facilities are needed.